Peak Fat Oxidation Rate Is Closely Associated With Plasma Free Fatty Acid Concentrations in Women; Similar to Men - Frandsen, Jacob; Poggi, Axel Illeris; Ritz, Christian; Larsen, Steen; Dela, Flemming; Helge, Jørn W. (Frontiers in Physiology, 2021)
Introduction: In men, whole body peak fat oxidation (PFO) determined by a graded exercise test is closely tied to plasma FFA availability. Men and women exhibit divergent metabolic responses to fasting and exercise and it remains unknown how the combined fasting and exercise affects substrate utilization in women. We aimed to investigate this, hypothesizing that increased plasma FFA concentrations in women caused by fasting and repeated exercise will increase PFO during exercise. And secondly, that PFO would be higher in women compared to men (Data from a previous study). Methods: On two separate days 11 young female athletes were investigated, either after an overnight fast (Fast) or 3.5 hours after a standardized meal (Fed). On each day a validated graded exercise protocol (GXT), used to establish PFO by indirect calorimetry, was performed 4 times each day separated by 3.5 hour of bedrest both in the fasted (Fast) or fed (Fed) state. Results: PFO increased in the fasted state from 113 (Fast 1) to163 (mean ± SD) mg/min/kg LBM (Fast 4) and this was highly associated with plasma FFA concentrations, which increased from 404203 (Fast 1) to 865210 mol/l (Fast 4). Compared to trained men from a former identical study we found no sex differences in relative PFO (mg/min/kg LBM) between men and women, in spite of significant differences in plasma FFA and glycerol concentrations during exercise after fasting. Conclusion: PFO increased with fasting and repeated exercise in trained women, but the relative PFO were similar in young trained men and women, despite major differences in plasma lipid concentrations during graded exercise.